Dekonstruksi Makna Feminisme Postmodern pada Puisi “Riḥlah Jabaliyyah, Riḥlah Șu’bah” Karya Fadwa Tuqan - Fikri, Alfikri Rausen Aditya; Haniah, Haniah; Kasim, Amrah; Hamzah, Nur Afifah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to analyze the poem “رحلة جبلية، رحلة صعبة” by Fadwa Tuqan using Jacques Derrida's deconstruction approach within the framework of postmodern feminist theory. The data source in this research is the poem رحلة جبلية، رحلة صعبة  by Fadwa Tuqan. The data collection technique employed is a literature study, which involves gathering data from writings sourced from articles, academic journals, and other relevant texts supporting the research. The data analysis technique used is content analysis. The analysis results show that Tuqan successfully deconstructs the essentialist construction of female identity and represents the female subject as an active and dynamic agent. From a postmodern feminist perspective, this poem rejects a singular narrative of womanhood and affirms plurality, performativity, and symbolic resistance through poetic language. This study recommends the importance of employing contemporary critical theories such as deconstruction and postmodern feminism in reading modern Arabic literary texts, especially women’s writings, to uncover the political and transformative potential embedded within the aesthetics of language.